STUDY COMMUNITY INVOLVEMENT IN DEVELOPMENT AGROTOURISM IN SEMBALUN - Krismon Nusantara Saksi ,; Prayitno Basuki ,; Handry Sudiartha Athar ,; Mahyuni, Mahyuni; Hairil Anwar , (International Journal of Social Science, 2025)
government support, and collaboration with the private sector. However, obstacles such as a lack of understanding of tourism management, limited promotion, and access to capital and technology are still challenges. Tourism potential such as strawberry picking, educational coffee and garlic tourism, as well as preserving traditional agricultural methods is considered very promising. The success of agrotourism is not only determined by the number of visitors, but also the quality of the experience provided. Therefore, the development of agrotourism in Sembalun needs to be carried out through product diversification, service improvement, digital promotion, empowerment of MSMEs, environmental preservation, and cross-sector collaboration to create inclusive and sustainable tourism.